2011
DOI: 10.1007/s00775-011-0827-2
|View full text |Cite
|
Sign up to set email alerts
|

Zn- and Cu-thioneins: a functional classification for metallothioneins?

Abstract: This report intends to provide the reader with a deeper insight in the chemical, and extensively biological, characteristics of the metallothionein (MT) system. We have devoted nearly 20 years to the study of MTs and this has allowed us to form what we believe is a more complete picture of this peculiar family of metalloproteins. At the beginning of the 1990s, the landscape of this field was quite different from the overall picture we have now. Many researchers have contributed to the readjustment of this part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 74 publications
2
133
0
5
Order By: Relevance
“…In Saccharomyces cerevisiae , cells are protected from the toxic effects of excess Cu by protein metallothioneins that contain cysteine rich residues, detoxifying Cu by coordination with multiple Cu ions [46]. While metallothioneins appear to play the major role in Cu resistance in S. cerevisiae , a putative metallothionein, CrdA, identified in A. nidulans did not exhibit a role in Cu detoxification [22].…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , cells are protected from the toxic effects of excess Cu by protein metallothioneins that contain cysteine rich residues, detoxifying Cu by coordination with multiple Cu ions [46]. While metallothioneins appear to play the major role in Cu resistance in S. cerevisiae , a putative metallothionein, CrdA, identified in A. nidulans did not exhibit a role in Cu detoxification [22].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the functional properties of MTs, it is a puzzling aspect that the metal-binding preferences of the proteins apparently cannot be attributed to unique amino acids in the secondary structure (Palacios et al, 2011). Also, the lack of protein data derived from native plant MTs with respect to localization and metalprotein stoichiometry consistently hampers the characterization of plant MTs and the clarification of their metabolic roles.…”
mentioning
confidence: 99%
“…Metallothioneins in mammals are responsible for the detoxi fi cation of cadmium, copper and zinc and have been proposed to be important in managing normal metal homeostasis [ 178,179 ] . The fi nal structure of metallated metallothioneins consists of two domains, an a and a b domain, de fi ned by the spacing of the cysteine residues and the number of metals coordinated.…”
Section: Sequestration and Regulationmentioning
confidence: 99%
“…The fi nal structure of metallated metallothioneins consists of two domains, an a and a b domain, de fi ned by the spacing of the cysteine residues and the number of metals coordinated. Metals bind in thiolate clusters that keep them in a biologically inert state [ 179 ] . Turnover of metallothionein occurs in the lysosome where the metals can be released back to the cytosol and some studies have suggested that metallothionein can be a direct source of metals for delivery within the cell independent of proteolysis [ 180 ] .…”
Section: Sequestration and Regulationmentioning
confidence: 99%